(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Recent systematic reviews of the literature and meta-analyses have found significant and nutritionally important compositional differences between conventional or organic foods. it includes high amounts of organic sources of omega-3 fatty acids meat and dairy items are also as higher antioxidant and reduced cadmium and pesticide indices of organic vegetables. Additionally, findings from a small number of human cohort studies show a link between eating organic food and a lower risk of developing some acute disorders, such as pre-eclampsia and hypospadias, as well as obesity. Concerns regarding possible harmful health effects of eating organic foods have also been voiced, but there is currently no evidence from human cohort studies to support these claims (risks related, for example, to decreased iodine levels in organic milk). However, there are virtually no data from (1) controlled human dietary intervention trials comparing the effects of organic and conventional diets, nor (2) long-term cohort studies focusing on chronic diseases (such as cardiovascular disease, diabetes, cancer, and neuro degenerative disorders). Therefore, it is currently hard to assess how much consuming organic food may impair one’s health.